Syphilis mimicking borderline (bt) leprosy. Historical, clinical and public health interfaces: interfaces quanto ao contexto histórico, clínico e de saúde publica - Schettini, Antonio P.M.; Sardinha, José C.G.; S. Júnior, Renato C.; Schettini, Maria C.A.; Lopes, Nádya F.P. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
We present a case of a 37 year-old woman, who was born and lived in Manaus, Brazil. She sought medical attention because of skin lesions – erythe-matous plaques of different sizes, localized to chest, face and lower limbs. A biopsy was performed and the hematoxylin and eosin staining hasshowed a granulomatous infiltrate around blood vessels, appendages and nerves. The pathological picture was considered to be compatible withtuberculoid leprosy. Correlation of the clinical and histological data lead to a diagnosis of borderline-tuberculoid leprosy and specific treatment wasstarted. The absence of clinical improvement after three months of treatment made the diagnosis to be reconsidered. A new study of the former slideswas performed and, in addition to the described abnormalities, it has shown a plasma cells infiltrate around blood vessels and in between the granulo-matous infiltrate. These abnormalities were not recognized at the first evaluation. With a reagent result of the VDRL (Venereal Disease ResearchLaboratory) test, the treatment of the leprosy was interrupted and syphilis was treated accordingly. After completion of treatment for syphilis, thelesions presented a progressive improvement Besides the case presentation, we analyze the different existing interfaces between syphilis and leprosy:(1) historical and public health interfaces and (2) clinical and laboratorial interfaces. We also stress the importance of these interfaces for the imple-mentation of control programs for these diseases.